Trade and environment: striking a balance in international law - Khanum, Farjina (2012)
This thesis seeks to balance trade and environmental concerns in international law. It studies a number of multilateral environmental and trade agreements to observe the extent to which environmental and trade treaty regimes have made allowances for each other's interests, and whether allowed such interests to be disregarded or overridden in practice. Serious questions remain, however, about the compatibility between overlapping environmental and trade rules in the absence of a clear authority relationship or means of securing unity in the international legal order as a whole. The international legal system does not possess well-developed hierarchies; thus, none of the agreements inherently takes precedence in the event of a conflict. Consequently, the aim should be to achieve a better harmonization of the two regimes through available mechanisms. The multilateral trade agreements have made allowances and included exceptions with regard to the protection of environmental concerns. However, the precise way in which trade institutions balance environmental considerations by comparison with trade considerations is likely to prove critically important for the protection of the environment. It is for this reason that this thesis analyses the current balance between trade and environmental considerations in the international legal order, and proposes ways for improving its coherence.